Por um ensino reflexivo e produtivo dos pronomes demonstrativos à luz da sociolinguística educacional - Fernandes, Mara Rúbia (2018)
This study had its origin in the confirmation thate the teaching of linguistic analysis, one of the four center lines guided by the National Curricular Parameters (BRASIL, 1997, 1998), does note occur in a satisfactory way in Braszilian public schools, either by the traditional and prescriptive approach of the language, present in the pedagogical materials available to the tacher, especially the textbook, or by the deficient sociolinguistic formation that the graduates of Letters receive during the graduation and that also does not occur in a satisfactory way in the training courses offered to the professors of Portuguese Language of Brazilian public schools. Therefore, the main objective of this research was to contribute to a more reflective and productive teaching about the real uses of the Portuguese Language and more adherent to the contemporary Brazilian variety, through the production of a notebook that contemplates the teaching of the linguistic topic "Demonstrative Pronouns "In the light of Educational Sociolinguistics (Cf. BORTONI-RICARDO, 2012, 2013, 2014) and the Pedagogy of Linguistic Variation (FARACO, 2009, 2017, BAGNO, 2009, 2014, 2015, 2016 and CYRANKA, 2007, 2015). Besides that, our objective was, specifically, study the guidelines proposed by the National Curriculum Parameters of Portuguese Language (BRASIL, 1997, 1998), mostly those related to Elementary Education II; to study the Municipal Curricular Guidelines (UBERLÂNDIA, 2011), observing, mainly, the orientations regarding the theme of the linguistic variation / diversity and the teaching of LP, from the perspective of the linguistic analysis; review the literature related to the teaching of Portuguese Language in Brazil, from a theoretical and applied point of view, focusing on those that deal with the attached questions of linguistic variation and Pedagogy of linguistic variation; research linguistic studies related to the pronominal system of Brazilian Portuguese in the light of Variationist Sociolinguistics; diagnose how students use demonstrative pronouns in writing; to propose didactic activities to the students researched – enrich to the research in the classroom –, in light of the important contributions of Educational Sociolinguistics to the teaching of the Portuguese Language in Brazil, focusing mainly on the uses of demonstrative pronouns in Contemporary Brazilian Portuguese; to make available a workbook that complements the textbook and presents reflections and exercises that contemplate the use of demonstrative pronouns in Contemporary Brazilian Portuguese, in different writing situations (more and less monitored contexts); contribute to the elaboration of Portuguese language teaching materials, focused on Basic Education, designed in the light of Educational Sociolinguistics; contribute to the formation of critical, reflective students and researchers of the language that they used in their daily life. For this, an action research was developed (see THIOLLENT, 2000), given its intervention and interpretative nature. Therefore, this research involved the participation of fifteen students of 8th grade from a public school of the municipal network of Uberlândia-MG -, besides the teacher-researcher. Over the course of two months, teaching activities of the "demonstrative Pronouns" were developed, planned in the didactic proposal elaborated by the researchers. In sequence, the data that composed the corpus of the research were analyzed: the students' answers and field notes of the teacher-researcher on the development of the activities. The analysis of the data showed that a didactic proposal for the teaching of linguistic analysis, in this specific case, the "Demonstrative Pronouns", proved to be an efficient pedagogical tool, as it contributed to the formation of a linguistic reflection capacity in the student, about the linguistic phenomenal present in real use.